The Primary Care Visit: What Else Could Be Happening? - Terry Fulmer; Patricia Cabrera (Hindawi Limited, 2012)
The Institute of Medicine Report called for a greater role for nurses within the context of oral health in two recent publications, Advancing Oral Health in America (2011) and Improving Access to Oral Health Care for Vulnerable and Underserved Populations (2011). Nurses provide care for many vulnerable persons, including frail and functionally dependent older adults, persons with disabilities, and persons with intellectual and developmental disabilities. These persons are the least likely to receive necessary, health-sustaining dental care (which is distinct from mouth care). The mouth, or more accurately, plaque, serves as a reservoir for bacteria and pathogens. The link between mouth care, oral health, and systemic health is well-documented; infections such as pneumonia have been linked to poor oral health. Nurses, therefore, need to reframe mouth care as oral infection control and infection control more broadly. The can provide the preventive measure that are crucial to minimizing systemic infections. Nurses in all settings can potentially provide mouth care, conduct oral health assessments, educate patients about best mouth care practices, and make dental referrals. Yet, nurses are often hesitant to do anything beyond basic oral hygiene-and even in this area, often fail to provide mouth care based on best practices.